Advancing Pharmacy Practice: The Role of Intelligence-Driven Pharmacy Practice and the Emergence of Pharmacointelligence - Hatem NAH (Dove Medical Press, 2024)
Najmaddin AH Hatem Department of Clinical Pharmacy, College of Clinical Pharmacy, Hodeidah University, Al-Hudaydah, YemenCorrespondence: Najmaddin AH Hatem, Department of Clinical Pharmacy, College of Clinical Pharmacy, Hodeidah University, Al-Hudaydah, 3114, Yemen, Tel +967775040472, Email clin.pharm.najmaddin@gmail.com; najmaddin@hoduniv.net.yeAbstract: The field of healthcare is experiencing a significant transformation driven by technological advancements, scientific breakthroughs, and a focus on personalized patient care. At the forefront of this evolution is artificial intelligence-driven pharmacy practice (IDPP), which integrates data science and technology to enhance pharmacists' capabilities. This prospective article introduces the concept of "pharmacointelligence", a paradigm shift that synergizes artificial intelligence (AI), data integration, clinical decision support systems (CDSS), and pharmacy informatics to optimize medication-related processes. Through a comprehensive literature review and analysis, this research highlights the potential of pharmacointelligence to revolutionize pharmacy practice by addressing the complexity of pharmaceutical data, changing healthcare demands, and technological advancements. This article identifies the critical need for integrating these technologies to enhance medication management, improve patient outcomes, and streamline pharmacy operations. It also underscores the importance of regulatory and ethical considerations in implementing pharmacointelligence, ensuring patient privacy, data security, and equitable healthcare delivery.Keywords: artificial intelligence in pharmacy, clinical decision support systems, pharmacy informatics, data integration in healthcare, personalized medication management, pharmacointelligence